Associated movement disorders in orthostatic tremor. Issue 7 (10th May 2012) - Mestre, Tiago A; Lang, A E; Ferreira, Joaquim J; Almeida, Vânia; de Carvalho, Mamede; Miyasaki, Janis; Chen, Robert; Fox, Susan
Abstract : Introduction: Orthostatic tremor is a rare tremor syndrome triggered exclusively by standing, with pathognomonic neurophysiological features. More recently, it has been suggested that orthostatic tremor can present either in isolation (pure orthostatic tremor) or associated with other movement disorders (orthostatic tremor-plus). The present study aims at expanding the knowledge concerning orthostatic tremor associated with other movement disorders. Methods: A retrospective case review of the clinical and neurophysiological data of patients diagnosed with orthostatic tremor. Results: Median age of onset was 61 years with a median diagnostic delay of 4.5 years. Orthostatic tremor-plus accounted for eight cases (30.8%). The associated movement disorders were Parkinson's disease (n=1), parkinsonism (n=1), progressive supranuclear palsy (n=1), restless leg syndrome (n=1), multifocal action tremor (n=2), pathological proven dementia with Lewy bodies (n=1) and focal dystonia of the arm (n=1). There were no significant differences between primary orthostatic tremor and orthostatic tremor-plus in demographics, clinical presentation of orthostatic tremor, findings in neurophysiological studies and response to treatment. In the majority of cases (n=18, 72%), there was a progressive and disabling course with refractoriness to medical therapy without significant differences between pure orthostatic tremor and orthostatic tremor-plus. Conclusion: One of the largest series on orthostatic tremor is presented and the second only focused on additional movement disorders. A progressive course was found, with increasing disability associated with orthostatic tremor. Dementia with Lewy bodies and task specific arm dystonia are reported for the first time as associated movement disorders.